Petrological basis for rank (maturity) determination of Permian coals from Pathakhera coal belt, Satpura Basin, M. P., India - Shukla, R. Rakesh; Siddharth, S. (Journal of Nepal Geological Society, 2001)
The Permian coals from the Pathakhera Coalfield are sub-bituminous to high volatile bituminous in rank based on chemical (i.e. carbon and volatile matter) and petrographic (i.e. reflectance) parameters. These coals are characterised by Type III kerogen maturity. The depth of burial of coal-bearing horizons varies from 2,200 to 3,100 m and the reflectance values of coals indicate 90-110 oC of maturation temperature.